Economic hardship and mental health following a national trauma and amid ongoing conflict: a longitudinal cohort study - Dana Katsoty; Yaakov Greenwald; Yuval Neria; Ariel Knafo-Noam; Ido Lurie (Social Psychiatry and Psychiatric Epidemiology, 2026)
Abstract Purpose Exposure to war and terrorism increases the risk of mental health problems and often leads to economic hardship, which can further heighten psychological distress. This longitudinal study examined the extent of economic hardship experienced during the Israel–Hamas war following the October 7th terrorist attack, the severity of mental health symptoms over the first year of the war, and the associations and temporal directionality between economic hardship and mental health. Methods A representative sample of Jewish Israeli adults ( N = 1,035) completed surveys at four time points: two weeks, and two, six, and 12 months after the attack. Participants reported economic hardship events (e.g., job loss, reduced income, unpaid leave, increased expenses, business losses) and symptoms of depression, anxiety, and posttraumatic stress disorder (PTSD). Results Psychological symptoms remained elevated throughout the year, declining from two weeks to two and six months after the attack, but rising again by 12 months. Economic hardship was prevalent and consistently associated with worse mental health outcomes. Longitudinal analyses showed a dynamic pattern: in the early stage of the war, poorer mental health predicted subsequent economic hardship, whereas later in the year, economic hardship predicted increases in depression, anxiety, and PTSD symptoms. Conclusion Psychological distress and economic hardship mutually influence one another across different stages of prolonged mass trauma. Integrating economic assistance with psychological support may help reduce long-term mental health impacts.